Nano-tungsten trioxide saturable absorber for L-band noise-like pulse mode-locked fiber laser - Abdul Hadi, M. A. W.; Lau, K. Y.; Mohd Yusoff, N.; Zainol Abidin, N. H.; Alresheedi, M. T.; Abas, A. F.; Goh, C. S.; Mahdi, M. A. (Academic Press, 2022)
We demonstrate the generation of noise-like pulse (NLP) in L-band erbium-doped fiber laser incorporating nano-tungsten trioxide and polydimethylsiloxane (WO3/PDMS) decorated onto a tapered fiber structure. A Raman pump unit with 3.5 W pump power was employed for a core-pumping scheme of 7 m long highly doped erbium-doped fiber. At the maximum pump power, the NLP lasing wavelength was at 1602 nm with a broad spectral bandwidth of 19.05 nm. The generated pulse was characterized to have 10.38 nJ energy and 19.66 mJ/cm2 output fluence. The measured NLP spike pulse width was 178.87 fs within 56.56 ps pedestal range. This work paves way for future development of generating NLP from nano-tungsten trioxide under extreme pump powers.